Optimization of Solid-state Fermentation Process of Polygonatum cyrtonema Hua by Lactobacillus bulgaricus and Its Effect on the Quality of Enzymatic Solution - Shengyu LIAO; Chenglin TANG; Yin QIN; Taiqiong GUO; Juanze HU; Guofei ZHU (Shipin gongye ke-ji, 2025)
To optimize the solid-state fermentation process of Polygonatum cyrtonema Hua by Lactobacillus bulgaricus and compare the quality of P. cyrtonema Hua enzymatic solution before and after fermentation, this study took the inoculation volume, fermentation temperature, and fermentation time as influencing factors, and used the 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging rate and total saponin content as evaluation indicators. Single-factor combined with Box-Behnken response surface methodology was used to optimize the fermentation process, and antioxidant activity and the content of bioactive substances were detected. The optimal process conditions for the fermentation of P. cyrtonema Hua by L. bulgaricus were an inoculation amount of 3%, a fermentation temperature of 38 ℃, and a fermentation time of 49 h. Under these conditions, the DPPH free radical scavenging rate of P. cyrtonema Hua enzymatic solution was 76.76%±1.49%, and the total saponin content was (5.00±0.01) mg/mL. After testing, the 2,2′-azino-bis-(3-ethylbenzothiazoline-6-sulfonic) acid (ABTS) cation free radical scavenging rate and total antioxidant capacity of the fermented P. cyrtonema Hua enzymatic solution were 90.10%±0.85% and (20.23±0.98) µmol/mL, respectively. The total phenolic, polysaccharide, and soluble solids contents were (93.44±5.46) µg/mL, (26.16±0.03) mg/mL, and (6.57±0.05)°Brix, respectively, which were higher than those of the unfermented group. After solid-state fermentation with L. bulgaricus, the antioxidant activity of P. cyrtonema Hua was enhanced, and the content of some bioactive substances increased.